Clinicopathological spectrum of Intracranial Posterior Fossa Tumours and their Prognostic significance: A Retrospective Institutional study at tertiary care hospital of Nalgonda District - Gubbala, Srinivas DD; Mattaparti, Sridevi; ., Bhavani (Annals of Pathology and Laboratory Medicine, 2019)
Background: Intracranial Posterior fossa tumors are critical brain lesions with significant neurological morbidity and mortality due to limited space and involvement of vital brain stem nuclei and fourth ventricle. Early diagnosis of posterior fossa tumors is vital to prevent potential risks of Brain stem compression, herniation, hydrocephalus and death. Aim of the study: 1. To study the morphological spectrum of intracranial posterior fossa SOLs. 2.To determine the frequency of posterior fossa SOLs reported in the tertiary care center of Nalgonda district. 3. To correlate clinical presentation with histopathological diagnosis and assess prognosis, and compare it with national and international literature. Materials and Methods: The present study was a retrospective description study conducted at the Department of pathology, Kamineni Institute of Medical Sciences, Narketpalli over a period of 3 years starting from June 2015 to June 2018. During this period, histopathological analysis of all the intracranial posterior cranial fossa tumors was done, correlated with clinical and radiological findings and prognosis assessed. Result: In our study Posterior fossa tumors are predominantly seen in adults with peak incidence in fourth decade. In children majority of the tumors were reported below 5 years of age. Most common presenting symptom was head ache and vomiting. Most common tumor was Medulloblastoma in children and Schwannoma in adults. Most common location was Cerebello-pontine angle followed by cerebellum. Recurrence rates were higher for CP angle tumors due to difficult sub-total resection. Prognosis is good for patients with total resection of tumors. Conclusion: Posterior fossa tumours are critical brain lesions with significant neurological morbidity and mortality. With rapid advancement in radiology and advent of modern therapeutic modalities early diagnosis and treatment is possible in many cases. Histopathology remains the gold standard in diagnosing Intracranial Posterior fossa tumours and necessary for the formulation of further management after neurosurgery.